Aromatic Candle-Making Training For Students Of State Senior High School 2 Sarmi In Tamar Sari, Bonggo Timur District, Sarmi Regency - gunaedi, tri gunaedi; Suyono, Joko; Farmawati, Farmawati; Tartillah, Baiq Amarwati (International Journal of Community Service (IJCS), 2025)
The natural resource processing industry in Bonggo District, Sarmi Regency, has begun to show results, particularly in the form of food products. A locally sourced industrial product that has not yet been tapped by industry players in Bonggo is the aromatherapy candles, made from essential oil extracts from Bonggo plants. Aromatherapy candles are generally used for aromatherapy, with their refreshing scent, and some even repel mosquitoes, depending on the essential oils mixed into the candles. Making an aromatherapy candle is simple, time-consuming, and requires inexpensive raw materials, with a high selling value compared to the raw materials. The training was conducted in collaboration with SMA Negeri 2 Sarmi, located in Tamar Sari Village, East Bonggo District, Sarmi Regency, Papua Province. The training aimed to train students, particularly 12th-grade students who were about to complete their high school studies. The knowledge gained from the training is expected to be developed into a business opportunity for those unable to pursue higher education. The training was conducted by providing material, and then continued with a trial of making aromatherapy candles carried out by the training participants. Evaluation was carried out by organoleptic testing of the level of preference for the resulting product in terms of aroma, smell, texture, and color, appearance using a Likert scale with a scale of 5, namely (1) Dislike, (2) Less like (3), Somewhat like, (4) Like, and Very like (5). The aromatherapy used was eucalyptus, citronella oil, tyme oil, coffee, and mosquito repellent aroma (soffel). The results achieved, most students were able to mix ingredients and make aromatherapy candles well and correctly. The organoleptic results stated that, in general, respondents showed their preference for the five aromatherapies in terms of aroma, texture, color, and smell.